1992
DOI: 10.21273/hortsci.27.12.1308
|View full text |Cite
|
Sign up to set email alerts
|

Cooling and Warming Effects on Cold Hardiness Estimations of Three Woody Ornamental Taxa

Abstract: Cooling treatments of 2, 4, and 6C/hour or warming at 25, 4, or 0C influenced the cold hardiness estimates of x Cupressocyparis leylandii (A.B. Jacks. and Dallim.) Dallim. and A.B. Jacks. (Leyland cypress), Lagerstroemia indica L. (crape myrtle), and Photinia ×fraseri Dress `Birmingham' (redtip photinia) at four times during the year. New growth from all taxa, especially spring growth, was injured or killed at higher tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
7
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 8 publications
2
7
0
Order By: Relevance
“…The dependence of the rise in deadly temperature caused by rapid cooling on a plant frost tolerance agrees with the findings of Haynes et al (1992). When plant tissues were submitted to rapid freezing, damage resulting from cell interior freezing may occur at higher temperatures where the rate of diffusion of water from the intracellular could not keep pace with the rate of temperature decrease (Levitt, 1980).…”
Section: Resultssupporting
confidence: 77%
“…The dependence of the rise in deadly temperature caused by rapid cooling on a plant frost tolerance agrees with the findings of Haynes et al (1992). When plant tissues were submitted to rapid freezing, damage resulting from cell interior freezing may occur at higher temperatures where the rate of diffusion of water from the intracellular could not keep pace with the rate of temperature decrease (Levitt, 1980).…”
Section: Resultssupporting
confidence: 77%
“…Whether freezing injury of even less cold-hardy plants remains unaffected by cooling rate cannot be inferred from our data. The dependence of the increase in lethal temperature caused by rapid cooling on a plant's cold hardiness agrees with the findings of Haynes et al (1992). These authors reported 2.5 to 3C difference in cold hardiness of crape myrtle (Lagerstroemia indica L.) stems cooled at 2 and 6C/h in January and March, but they did not detect significant differences between slow and fast cooling in October and August when plants were less cold hardy.…”
Section: Resultssupporting
confidence: 86%
“…Sample temperature was recorded by thermocouples placed next to the stem or leaf. To avoid excessive supercooling of tissue water, when the temperature of the samples stabilized overnight at -2.0 ± 0.5C, the samples Rapid cooling may increase the degree of freezing injury in plants (Chen and Gusta, 1978;Havis, 1964;Haynes et al, 1992;Krasavtsev, 1973;Levitt, 1980;Slater and Warmund, 1986;Steffen et al, 1989;Warrington and Jackson, 1981;White and Weiser, 1964). Freezing plants >5C/h has been classified as rapid cooling (Levitt, 1980).…”
Section: Methodsmentioning
confidence: 99%
“…Resistance indices, such as the temperature at 50% lethality (LT 50 ) (Levitt, 1972), the lowest survival temperature (LST) (Quamme et al, 1972), or the temperature interval between 10% and 90% injury (Ketchie et al, 1972), are desirable in studying the acclimation-deacclimation process or the effects of environmental stimuli on the degree of frost resistance. However, in many cases, the resistance indices are estimated graphically from temperature curves (e.g., Haynes et al, 1992;Montano et al, 1987;Ritchie et al, 1985). The shortcomings of these graphic methods are that there is an inclination to subjective bias errors, only rough estimates are produced, and the degree of confidence associated with the resistance index cannot be estimated.…”
Section: Methodsmentioning
confidence: 99%